Komunikasi Humas Sekertariat Presiden Republik Indonesia Melalui Unggahan Foto Kegiatan Presiden Dalam Mencegah Berita Hoax - Siti Sarah Destyani; Maman Suherman (Bandung Conference Series: Public Relations, 2022)
Abstract. A government institution in Indonesia has its own functions and functions, all of which help develop the Vision and Mission as well as the Goals to be achieved by the President of the Republic of Indonesia. The researcher found one object in this qualitative research, namely the Public Relations of the Presidential Secretariat of the Republic of Indonesia which is operationally carried out by the Biro Pers Media dan Infromasi. News about the activities of the President of the Republic of Indonesia is information that supports the public for the entire community, not only news that has positive values ​​on the negative side. However, until now there are many people who do not fully understand how to take really good information and/or obtain valid data sources. So that there are still many individuals or media who spread hoax news about the President of the Republic of Indonesia for their personal gain. Therefore, the PR of the Presidential Secretariat, especially the Press, Media and Information Bureau, has a way of communication in building a good public view of every activity carried out by the President of the Republic of Indonesia by utilizing social media through digital platforms, namely the presiden.go.id website and YouTube Setpres to publish and release of the results of the appropriate activities of the President of the Republic of Indonesia that occurred in the field along with clear data and facts. This study uses a qualitative method with a case study approach. Data collection techniques were carried out by means of observation, interviews, documentation and literature study. The results of this study are 1) Communication of the Public Relations of the Secretariat of the President of the Republic of Indonesia carried out by the Biro Pers Media dan Infromasi in disseminating information through the presidential.go.id website and the YouTube Setpres has been planned and systematic 2) In the process of making news, the form of activities that can be disseminated to the community is in accordance with the needs of the community and in accordance with applicable laws. 3) The barriers to PR practitioners at the Secretariat of the President of the Republic of Indonesia, namely the Biro Pers Media dan Infromasi, have been coordinated according to the communication strategy that was developed. Abstrak. Sebuah Lembaga pemerintahan di Indonesia memiliki fungsi dan tugasnya masing-masing, semua membantu mengembangkan Visi dan Misi serta Tujuan yang ingin di capai oleh Presiden Republik Indonesia. Peneliti menemukan salah satu objek dalam penelitian kualitatif ini yaitu Humas Sekertariat Presiden Republik Indonesia yang secara operasional dilakukan oleh Biro Pers Media dan Informasi. Berita mengenai kegiatan Presiden RI adalah infromasi yang menunjang keterbukaan public kepada seluruh masyarakat, tidak asing setiap berita tidak hanya memberitakan berita yang bernilai positif saja melainkan sisi negatifnya. Namun hingga saat ini banyak sekali masyarakat yang belum memahami sepenuhnya dalam mengambil informasi yang baik dan benar/valid sumber data yang diperoleh. Sehingga masih banyak sekali oknum atau media-media yang menyebarkan berita hoax mengenai Presiden RI demi keuntungan pribadinya. Oleh karena itu Humas Sekertariat Presiden khususnya Biro Pers Media dan Infromasi memiliki cara komunikasi dalam membangun pandangan masyarakat yang baik terhadap setiap kegiatan yang dilakukan oleh Presiden RI dengan memanfaatkan adanya media sosial melalui platform digital yaitu website presiden.go.id dan youtube Setpres untuk mempublikasikan dan release hasil kegiatan Presiden RI yang sesuai terjadi di lapangan beserta data dan fakta yang jelas. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara, dokumentasi dan studi kepustakaan. Hasil dari penelitian ini adalah 1) Komunikasi Humas Sekertariat Presiden RI yang dilakukan oleh Biro Pers Media dan Infromasi dalam memberitakan Informasi melalui website presiden.go.id dan youtube Setpres sudah terencana dan sistematis 2) Dalam proses pembuatan berita , bentuk kegiatan yang mampu disebarkan kepada masyarakat sudah sesuai dengan kebutuhan masyarakat dan sesuai dengan perundang-undangan yang berlaku 3) Hambatan praktisi Humas Sekertariat Presiden RI yaitu Biro Pers Media dan Infromasi sudah terkoordinir sesuai dengan strategi komunikasi yang dibangun.